Hoani and Hiwa - Anneff, Katarina (Te Kaharoa, 2021)
“Hoani time to get up.” Dang it Mum it’s the weekend. “What did you say boy?” Oh, shit. Did I say that out loud? “Sorry Mum!” Far out. Why are we getting up so early for, it’s legit only 6am. “Ok you three have 10 minutes to pack your bags and get in the car. Kia tere!” The only time we get up this early is when we go home to the Hokianga to see Koro. DANG IT. Why are we going to Koro’s house man, it’s so boring up there. I haven’t been back home to Hokianga since I was 10, I’m 14 now. Turns out we’re going to Koro’s to celebrate Matariki, the Māori New Year. Sounds boring aye. Yeah, thought so hahahaha.